PENGARUH PENERAPAN PENDEKATAN TPACK TERHADAP HASIL BELAJAR PESERTA DIDIK MATERI PECAHAN KELAS V SEKOLAH DASAR NEGERI 27 PONTIANAK UTARA - Yavira Zahwa Primadia; Bistari; Asmayani Salimi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of the Application of the TPACK (Technological Pedagogical Content Knowledge) Approach on the Learning Outcomes of Fraction Materials in Class V of State Elementary School 27 North Pontianak. The research method used was an experiment with the form of Quasi-Experimental Design with the type of Nonequivalent Control Group Design. The population is class V of State Elementary School 27 North Pontianak. The sampling technique in this study was Probality Sampling with Simple Random Sampling type. The data collection technique used was measurement technique and the data collection tool was a written test in the form of an essay. Based on data analysis, the average results of the final test of the experimental class and control class were obtained. The results of hypothesis testing using independent sample t-test obtained sig 0.27 > 0.05 so that Hₒ is rejected and Hₐ is accepted. This proves that there is an effect of the application of the TPACK (Technological Pedagogical Content Knowledge) approach on the learning outcomes of students in class V fraction material at North Pontianak 27 State Elementary School. Based on the results of the calculation of the effect size obtained 0.8 which is included in the medium criteria. Thus, it can be concluded that the TPACK approach model provides a helpful influence on the learning outcomes of grade V students of North Pontianak 27 State Elementary School.